THE DIASPORA SENSIBILITY IN TEACHER IDENTITY: LOCATING SELF THROUGH STORY - Kooy, Mary; de Freitas, Elizabeth (Canadian Journal of Education/Revue canadienne de l’éducation, 2007)
The concept of diaspora describes the dispersal of persons from their traditional homeland, across national and cultural borders. We explore disasporic (dis)location as it disrupts and recreates teacher identity. The nomadic movement across borders in professional development is best understood through narrative; hence we examine the self‐constructed narratives of three participants in a graduate class representing diverse cultural backgrounds who traced their complex and shifting teacher stories as a construct to understand the complex shifts in their identities. In a rapidly changing global migration, these narratives provide insight into the navigations and negotiations of diasporic journeys and shifting, evolving perceptions of teacher identities. Key words: teacher learning, narrative as heuristic, dialogic, transnational migration, transnational dislocation Le concept de diaspora évoque la dispersion des personnes loin de leur pays d’origine et le franchissement de frontières nationales et culturelles. Les auteures explorent la dislocation de la diaspora et son lien avec la rupture et la recréation de l’identité d’enseignant. Le nomadisme au‐delà des frontières dans le perfectionnement professionnel se comprend mieux à travers des récits ; les auteures examinent donc les comptes rendus personnels de trois participants dans un cours du second cycle universitaire. Venus d’horizons culturels différents, ces participants relatent leurs histoires complexes sous le signe du changement comme un construit visant à élucider la transformation de leurs identités. Compte tenu de l’évolution rapide et complexe de la migration à l’échelle internationale, ces récits permettent de mieux saisir les navigations et négociations des périples de la diaspora et l’évolution des perceptions des identités des enseignants. Mots clés : apprentissage chez les enseignants, récit et migration heuristique, dialogique et transnationale, dislocation transnationale.